China's "discourse power" strategy: taking China's Twitter publicity as a case - Zheng, Jiayu (2022)
To strengthen china's external publicity, Xi Jinping has mobilized massive resources to secure China's interests and reinforce its reputation both at home and abroad. This dissertation inquiries into why and how China's Ministry of Foreign Affairs during the outbreak of COVID-19 pandemic era has been actively engaged in conducting online publicity by means of disseminating good images of China on Twitter. The analysis part illuminates the features of linguistic tendency in publicizing, narrative style and Xi's idea of "discourse power" strategy for "telling China's stories well (jianghao zhongguo gushi, 讲好中国故事)". In response to the need to enhance China’s discourse power, various propaganda approaches have been adopted and the impacts of China have been increased on some levels. Two spokespersons of the Ministry of Foreign Affairs (Hua Chunying and Zhao Lijian) as well as two Chinese state-owned mainstream media (CGTN and China Daily) play major roles in the construction of Twitter publicity fronts which serves China's diplomatic purposes. Three systemic analysis methods, which are interpersonal systemic analysis, modality systemic analysis and evidentiality analysis, are adopted to deconstruct and reclassify the text content of Hua and Zhao’s Tweets, and to observe and deduce the characteristics of "discourse power" strategy. Though a number of exploratory approaches to influencing foreign targeted audiences have been taken, China failed to achieve the desired effects; the COVID-19 publicity has further exacerbated the mutual political misunderstanding between China and the United States.